Factors influencing the addiction characteristics of non-suicidal self-injurious behaviors in adolescents: A case-control study - Zhu, Junhong; Qian, Rui; Zhong, Hao; Li, Yi; Liu, Xuebing; Ma, Jun (Frontiers in Psychiatry, 2022)
Background: Many studies have shown that in the context of public health emergencies, the incidence rate of adolescent non-suicidal self-injury (NSSI) patients increased dramatically. This paper aims to characterize the behavioral characteristics of adolescent NSSI and analyze the influencing factors of NSSI behavior addiction characteristics. Methods: The study design was a case-control study that included 84 adolescent NSSI patients and 84 controls. The differences in the scores of the following five scales were compared between the case and control groups: Egna Minnen Barndoms Uppfostran (EMBU), Perceived Social Support Scale (PSSS), Perceived Stress Scale (PSS); Bergen Social Media Addiction Scale (BSMAS) and Video Game Dependence Scale (VDG-S). The characteristics of NSSI behavior of the study group were evaluated using the Ottawa Self Inventory Chinese Revised Edition (OSIC). And a binary logistic regression model was developed to analyze the factors that influence adolescent NSSI behavioral addiction characteristics. Results: Compared to the controls, in the study group, the emotional warmth scores in the father's and mother's rearing style scores in the EMBU were significantly lower. The BSMAS and VDG-S scores were significantly higher than in the control group. In the study group, 38 cases of NSSI with addiction characteristics accounted for 45.24%. The risk factors for NSSI addiction traits were as follows: female, single-child, high level of VDG-S scores, high scores of excessive interferences in father’s rearing style, and high scores of punishments and excessive interferences in mother’s rearing style score. Conclusion: Female, an only child, internet addiction, and negative parenting styles all had a negative impact on the development of NSSI behavioral addiction characteristics in adolescent NSSI patients. Mental health providers and parents should develop targeted coping strategies for negative parenting styles among female adolescents in one-child families to reduce the occurrence and development of NSSI behaviors.